Advances in Immunotherapy for Melanoma: A Comprehensive Review - Carmen Rodríguez-Cerdeira; Miguel Carnero Gregorio; Adriana López-Barcenas; Elena Sánchez-Blanco; Beatriz Sánchez-Blanco; Gabriella Fabbrocini; Brunilda Bardhi; Ardiana Sinani; Roberto Arenas Guzman (Mediators of Inflammation)
Melanomas are tumors originating from melanocytes and tend to show early metastasis secondary to the loss of cellular adhesion in the primary tumor, resulting in high mortality rates. Cancer-specific active immunotherapy is an experimental form of treatment that stimulates the immune system to recognize antigens on the surface of cancer cells. Current experimental approaches in immunotherapy include vaccines, biochemotherapy, and the transfer of adoptive T cells and dendritic cells. Several types of vaccines, including peptide, viral, and dendritic cell vaccines, are currently under investigation for the treatment of melanoma. These treatments have the same goal as drugs that are already used to stimulate the proliferation of T lymphocytes in order to destroy tumor cells; however, immunotherapies aim to selectively attack the tumor cells of each patient. In this comprehensive review, we describe recent advancements in the development of immunotherapies for melanoma, with a specific focus on the identification of neoantigens for the prediction of their elicited immune responses. This review is expected to provide important insights into the future of immunotherapy for melanoma.